Pengaruh Corporate Social Responsibility (CSR) Terhadap Citra Perusahaan PT. PLN (Persero) Di Kota Medan Pada Awal Tahun 2025 - Adinda; Damanik, Cindy Tasya; Siregar, Wulandari; Mas'ut; Ramadhani, Nu rika (Jurnal Riset Mahasiswa Akuntansi, 2025)
This study examines how Corporate Social Responsibility (CSR) affects the perception of PT. PLN (Persero) in Medan City in early 2025. Secondary data collection (literature 2017–2025) and primary data through 60 respondents in the CSR beneficiary community by applying a quantitative approach. With data analysis carried out by applying multiple linear regression with SPSS V20. The findings from the validity and reliability tests indicate that the instrument is valid (R count is greater than R table 0.2542) and reliable (Cronbach Alpha is greater than 0.60). In addition, the multicollinearity and normality tests are met. Heteroscedasticity tests do not occur; however, the partial T test shows that economic responsibility (H1) and social responsibility (H2) do not have a significant impact on the company's image partially; on the contrary, the F test shows that economic responsibility and social responsibility have a positive and meaningful impact on the company's image simultaneously. Thus, PT. PLN (Persero) can be improved by implementing both responsibilities simultaneously.